ANALISIS ISO 9001:2015 PT PANCA BINTANG TUNGGAL SEJAHTERA DENGAN MENGGUNAKAN METODE GAP ANALYSIS - Yunita Primasanti; Rachmat Hendratmoko (Jurnal Disprotek, 2021)
Large and medium scale companies wish to obtain ISO 9001: 2015 certificate to improve management quality. PT Panca Bintang Tunggal Sejahtera has made preparations for the implementation of quality management. Before applying for the certification process, the company has implemented and is currently reviewing the implementation of its quality management system so that the certification process can run well so that the certificate can be obtained. To analyze the level of implementation of the quality management system in the company used the GAP analysis checklist method. This analysis uses several indicators. Furthermore, interviews were conducted with each director who served in the company to determine the obstacles in the application of the quality management system. The results of the GAP analysis checklist show that the implementation of the ISO 9001: 2015 quality management system in the company is good but still requires improvement in several clauses. The percentage of the assessment shows that clause 9 (performance evaluation) is the clause with the lowest score with a value of 60.25%, while the highest percentage is in clause 5 (leadership) with a score of 81.29%. The main obstacle faced by the company is the level of understanding of the implementation of the new system is still lacking and the performance of some individuals is not optimal. Companies must be more intense in monitoring the performance of each unit to improve their quality management system so that the certification process can run smoothly.